Diaromatic sulphur-containing 'naphthenic' acids in process waters - West, C.; Scarlett, Alan; Tonkin, A.; O'Carroll-Fitzpatrick, D.; Pureveen, J.; Tegelaar, E.; Gieleciak, R.; Hager, D.; Petersen, K.; Tollefsen, K.; Rowland, S. (2014)
Polar organic compounds found in industrial process waters, particularly those originating from biodegraded petroleum residues, include 'naphthenic acids' (NA). Some NA have been shown to have acute toxicity to fish and also to produce sub-lethal effects. Whilst some of these toxic effects are produced by identifiable carboxylic acids, acids such as sulphur-containing acids, which have been detected, but not yet identified, may produce others. Therefore, in the present study, the sulphur-containing acids in oil sands process water were studied.A fraction (ca 12% by weight of the total NA containing ca 1.5% weight sulphur) was obtained by elution of methylated NA through an argentation solid phase extraction column with diethyl ether. This was examined by multidimensional comprehensive gas chromatography-mass spectrometry (GCxGC-MS) in both nominal and high resolution mass accuracy modes and by GCxGC-sulphur chemiluminescence detection (GCxGC-SCD).Interpretation of the mass spectra and retention behaviour of methyl esters of several synthesised sulphur acids and the unknowns allowed delimitation of the structures, but not complete identification. Diaromatic sulphur-containing alkanoic acids were suggested.Computer modelling of the toxicities of some of the possible acids suggested they would have similar toxicities to one another and to dehydroabietic acid. However, the sulphur-rich fraction was not toxic or estrogenic to trout hepatocytes, suggesting the concentrations of sulphur acids in this sample were too low to produce any such effects invitro. Further samples should probably be examined for these compounds. © 2013 Elsevier Ltd.